2022
DOI: 10.1177/15579883211070383
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Daytime Ingestion of Melatonin on Thyroid Hormones Responses to Acute Submaximal Exercise in Healthy Active Males: A Pilot Study

Abstract: It is well known that exercise increases the activity of thyroid glands and raises the blood level of melatonin. The increase of melatonin during exercise may be linked to a rise in thyroid-stimulating hormone (TSH). No previous study has investigated the combined effects of melatonin ingestion and acute submaximal exercise on thyroid hormones’ responses. The purpose of this pilot study was to explore the effects of daytime ingestion of melatonin on thyroid hormones’ responses to acute submaximal exercise. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, in contrast to the group treated with myoinositol alone (2g/day), it was observed that the addition of melatonin increased the level of TSH over the six-month treatment period (68). In a recent study, daytime acute melatonin ingestion (6 mg) before 50 min of submaximal exercise did not influence the responses of thyroid hormones to exercise (69).…”
Section: Melatoninmentioning
confidence: 82%
“…Furthermore, in contrast to the group treated with myoinositol alone (2g/day), it was observed that the addition of melatonin increased the level of TSH over the six-month treatment period (68). In a recent study, daytime acute melatonin ingestion (6 mg) before 50 min of submaximal exercise did not influence the responses of thyroid hormones to exercise (69).…”
Section: Melatoninmentioning
confidence: 82%
“…Although melatonin has numerous good effects (23,66), there have been some isolated reports of a few unpleasant side effects (e.g., a modest increase in blood pressure due to nitric oxide synthase downregulation) (37,45,46,50,51). Notably, it is well recognized that diurnal melatonin ingestion in young healthy men might result in sleepiness, weariness, alertness deficiency, loss of balance, and poor coordination (35,46).…”
Section: Adverse Occurrences Related To Oral Melatonin Dosingmentioning
confidence: 99%
“…Beyond sleep, the LC has been linked to fluctuations in various biological markers. [ 9 10 11 ] For instance, melatonin, often referred to as the “sleep hormone,” plays a crucial role in regulating sleep–wake cycles. [ 11 ] This hormone, which is primarily secreted by the pineal gland, is instrumental in determining sleep onset and duration.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 10 11 ] For instance, melatonin, often referred to as the “sleep hormone,” plays a crucial role in regulating sleep–wake cycles. [ 11 ] This hormone, which is primarily secreted by the pineal gland, is instrumental in determining sleep onset and duration. [ 11 ] In children, melatonin not only governs sleep but also plays a role in developmental processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation